2021
DOI: 10.1002/star.202100126
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Pleurotus ostreatus Mushroom—Wheat Bread

Abstract: The Pleurotus ostreatus mushroom is a source of high nutritional value and bioactive compounds such as 𝜷-glucans, with immunomodulatory, hypoglycemic, and prebiotic activity. The aim of this work is to develop a bread with P. ostreatus powder (POP) to increase its nutritional value and reduce its glycemic index. Four formulations are proposed substituting 5%, 10%, 15%, and 20% of wheat flour (w/w) for POP in the bread. Their physical and nutritional characteristics were evaluated. In addition to determining t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
2
2
0
Order By: Relevance
“…Results indicated that there was no significant effect of DMP addition on fat and NFE contents of all breadsticks treatments. These findings are in agreement with those reported by Losoya-Sifuentes et al [56], where adding mushroom flour to bread increased moisture, ash, fat, and protein contents.…”
Section: Chemical Composition Bioactive Compounds Andsupporting
confidence: 94%
See 1 more Smart Citation
“…Results indicated that there was no significant effect of DMP addition on fat and NFE contents of all breadsticks treatments. These findings are in agreement with those reported by Losoya-Sifuentes et al [56], where adding mushroom flour to bread increased moisture, ash, fat, and protein contents.…”
Section: Chemical Composition Bioactive Compounds Andsupporting
confidence: 94%
“…These findings might be because DMP was a good source of polyphenol compounds and flavonoids as shown in Table 4. The data obtained in the present study are in agreement with those reported by Losoya-Sifuentes et al [56] who found that bread fortified with mushroom powder showed a significant increase (P ≤ 0:05) in the redness and yellowness values. This may be due to chemical reactions that occur during baking, between the phenolic compounds, the sugars, and proteins contained in the mushroom, thus altering the final color of the product.…”
Section: Color Measurement Of Waffles Breadsticks and Saladsupporting
confidence: 93%
“…For example, an increase in the antioxidant properties of pasta has been confirmed when mushrooms are added to their composition [10]. A decrease in the glycemic index of bread has been experimentally proven when a mushroom component is added to the recipe [11].…”
Section: Introductionmentioning
confidence: 94%
“…In more recent studies, a wheat bread with P. ostreatus powder was developed to increase its nutritional value and reduce its glycemic index. The nutritional value of the bread was enriched since the protein, fiber, and mineral content increased [51].…”
Section: Breadmentioning
confidence: 99%